Behavioral responses of predaceous minute pirate bugs to tridecane, a volatile emitted by the brown marmorated stink bug - Fraga, Diego F. [UNESP]; Parker, Joyce; Busoli, Antonio C. [UNESP]; Hamilton, George C.; Nielsen, Anne L.; Rodriguez-Saona, Cesar (Springer Nature, 2017)
Since its introduction from Asia, the brown marmorated stink bug, Halyomorpha halys (Stål), has become a pest of many agricultural crops in the USA. Insect predators utilize H. halys as prey; however, the chemical cues used by them in prey location are largely unknown. Here, we hypothesized that tridecane, an H. halys-associated volatile, acts as a kairomone for the predaceous minute pirate bug, Orius insidiosus (Say). We conducted laboratory, greenhouse, and field experiments to: (1) assess the attraction of adult O. insidiosus to H. halys-damaged bean pods and tridecane in cage studies, and its effect on egg predation; (2) video record the behavioral response of O. insidiosus males and females to tridecane in a four-arm olfactometer; and (3) test whether Orius spp. are attracted to tridecane-baited sticky traps in peach, blueberry, and sunflower fields, and its effect on egg predation. In the greenhouse, O. insidiosus was attracted to H. halys-damaged pods and artificial plants baited with tridecane in the presence of prey (sentinel eggs); however, this attraction rarely led to increased egg predation. Although both O. insidiosus males and females spent more time in the arm of the olfactometer with tridecane, males were more responsive at a lower concentration than females. Similarly, Orius spp. were more attracted to tridecane-baited than unbaited traps in the field; however, there was no effect on egg predation. Altogether, while O. insidiosus is attracted to tridecane, this attraction did not always lead to higher predation, suggesting that this kairomone likely acts as an arrestant.
Keywords: BMSB; Conservative biological control; Halyomorpha halys; Invasive pests; Kairomones; Orius insidiosus